Vascular reconstruction of the decellularized biomatrix for whole-organ engineering—a critical perspective and future strategies - Gupta, Santosh; Sharma, Akriti; Petrovski, Goran; Verma, Rama Shanker (Frontiers in Bioengineering and Biotechnology, 2023)
Whole-organ re-engineering is the most challenging goal yet to be achieved in tissue engineering and regenerative medicine. One essential factor in any transplantable and functional tissue engineering is fabricating a perfusable vascular network with macro- and micro-sized blood vessels. Whole-organ development has become more practical with the use of the decellularized organ biomatrix (DOB) as it provides a native biochemical and structural framework for a particular organ. However, reconstructing vasculature and re-endothelialization in the DOB is a highly challenging task and has not been achieved for constructing a clinically transplantable vascularized organ with an efficient perfusable capability. Here, we critically and articulately emphasized factors that have been studied for the vascular reconstruction in the DOB. Furthermore, we highlighted the factors used for vasculature development studies in general and their application in whole-organ vascular reconstruction. We also analyzed in detail the strategies explored so far for vascular reconstruction and angiogenesis in the DOB for functional and perfusable vasculature development. Finally, we discussed some of the crucial factors that have been largely ignored in the vascular reconstruction of the DOB and the future directions that should be addressed systematically.